Perfect fluid models of Bianchi type-VI0 in modified Brans-Dicke cosmology - Ram S. (My University, 2025)
The spatially homogeneous and anisotropic Bianchi type-VI0 cosmological solution for barotropic fluid in the context of modified Brans-Dicke theory is obtained. The general behavior of such an anisotropic homogeneous model has been discussed. © 1986 American Institute of Physics.